Increase in resistance of Mycoplasma hominis to tetracyclines. - Cummings, M C (1990)
Isolates of Mycoplasma hominis collected from patients in Boston and New York between 1976 and 1989 were studied. Minimal metabolism-inhibiting concentrations (MMCs) were determined by use of a terminal color change-broth dilution method, as well as by an agar inoculum-broth dilution method. Both methods gave comparable results. Tetracycline MMCs for 3 (7.0%) of 43 isolates of M. hominis collected from 1976 to 1979 were 8 micrograms/ml or more, but they were 8 micrograms/ml or more for 11 (20.3%) of 54 isolates collected from 1980 to 1983 (P = 0.083) and 16 (26.6%) of 60 isolates collected from 1984 to 1989 (P = 0.019). Similarly, doxycycline MMCs for 0 of 43 isolates of M. hominis collected from 1976 to 1979 were 8 micrograms/ml or more, but they were 8 micrograms/ml or more for 8 (14.8%) of 54 strains isolated from 1980 to 1983 (P = 0.0082) and 10 (16.6%) of 60 strains isolated from 1984 to 1989 (P = 0.0047). The susceptibility of M. hominis to clindamycin did not change. We conclude that isolates of M. hominis in the northeastern United States have become more resistant to tetracycline and doxycycline over the past decade.